Trust and Distrust in a Democratic State of Law - Marta Krasoń; Robert Krasoń (Acta Universitatis Lodziensis Folia Iuridica)
The issue of trust in law and trust of the governed in those who govern them has accompanied mankind since the early history. Trust is one of the most prominent values for maintaining cohesion of social groups and, more broadly, whole societies. People had to first have trust in themselves in order to trust the law and the state and, eventually, to have the state to trust them. The matter of trust in law remains highly up-to-date and should be considered in connection with the trust in the lawmakers, the legal acts created by them, but also trust in law exhibited by the relevant institutions and bodies. Trust is a temporal state; we can enjoy it either permanently or periodically, therefore, the institutions and principles laid down by the law are an indispensable aspect that guarantees permanence of trust. The key task of public administration, aimed at inspiring and intensifying trust, is to obtain and secure the common good in the state on the basis of, and within the limits of, the applicable legal regulations, which at the same time set out the methods and scope of social protection in the individual spheres of operation of the legislative, executive, and judicial authorities.